Relationship Between Tight Pants Use and The Incidence of Flour Albus Pathology in Women of Childbearing Age - Marni Br Karo; Ai Nuraida; Lenny Irmawaty Sirait; R. Haryo Bimo Setiarto (Jurnal Kesehatan Prima, 2021)
Women who have not had a marital relationship, vaginal discharge can also occur, but the cause of leucorrhoea can occur because of using tight pants, wearing a towel together, the lack of maintaining the cleanliness of the vaginal area. This study aims to determine the association of the vulva higiene with vulvovaginal candidiasis on fertile age in Public Health Center (PHC) Cipayung districts. This study aim to know the relationship of the use of tight pants with the incident flour albus pathology in women of childbearing age at the PHC Cipayung. The analytic study method with study design was cross sectional approach and chi square test would be used. The research using purposive sampling by through 36 women of childbearing. This data used is primary data. The result showed that there is a significant association between tight pants use with flour albus pathology incidence in women of childbearing age at the PHC Cipayung (P-value = 0.009; α = 0.05). There is a relationship between vulva hygiene and vulvovaginal candidiasis at Cipayung PHC due to lack of vaginal hygiene on woman of childbearing age, which increased the incidence of candidiasis.